Religious coping strategies and perceived causes of sickness and health in South Africa - Peet J. van Dyk; Alta C. van Dyk (Verbum et Ecclesia, 2015)
The purpose of this survey was to explore religious coping strategies and to what extent black South Africans directly attributed their health and/or diseases to supernatural forces such as the ancestors and magic. A total of 3000 structured questionnaires were distributed to South Africans of all ethnicities, of which 575 were received back, but only those received from black participants (411) were considered for this study. The SPSS 21 statistical program was used to analyse the data. The results of the study suggest that Mbitis remark that health and disease in Africa are seen primarily within a religious (i.e. supernatural) framework still holds true for the black South African participants in this study. More than 80% (81.5%) of the participants attributed their health and diseases primarily to the ancestors and magic,whilst only 16.1% of the participants ascribed any importance to natural causes of diseases(e.g. germs and unprotected sex). These beliefs were especially strong amongst city or town dwellers, people of higher educational level and members of so-called mainline churches (i.e.members of non-Zionist churches). Intradisciplinary and/or interdisciplinary implications: The article is interdisciplinary in nature covering the following fields: religion, psychology; health studies.